Analysis of Government Policy on Green Open Space in Bekasi City - Sarofah, Riska; Ayu Herliana, Priska (Jurnal Studi Ilmu Pemerintahan, 2023)
This paper explains the green open space policy that, as a regional environmental ecosystem controller, calls for a structural solution. Green open space policy number 10 for Bekasi City in 2011 with regards to order, cleanliness, and attractiveness. Only 15% of the required green open space has been achieved, even though the norm should have been 30%. Through the Bekasi city regional regulation (PERDA) number 13 of 2011, the Bekasi city government established a rule pertaining to the Bekasi city development plan to achieve 30% of green open space (RTH), with specifics of 20% for green open space and 10% for public space. In this study, a qualitative technique was employed to collect the data. Descriptive analysis was then performed to analyse the data using the N-Vivo 12 Plus program. A variety of trustworthy and pertinent sources, including websites, journals, publications, and online media news analysts, were used to gather the data. The study's findings suggest that a number of factors, including the presence of citizens, financial resources or APBD, geographical circumstances, area size, and priority programs, affect the amount of green open space in the city of Bekasi. Regulations and the expansion of the green open space area are two variables that affect the availability of green space in Bekasi. The development of must involve a number of groups, including the community, the private sector, and the local government green open spaces so that the target of green open spaces in the city of Bekasi can be achieved